Long-term spatiotemporal features of aerosol optical characteristics and relative humidity in China’s offshore areas - Jie He; Zhao Li; Linyu He; Jian Wang; Weiping Jiang (Geo-spatial Information Science)
Marine aerosols are crucial for ocean–atmosphere interactions. However, there is a lack of analysis on the long-term aerosol optical characteristics and relative humidity (RH) based on large-scale ocean regions. This paper addresses this issue by analyzing the spatiotemporal variations of aerosols in China’s offshore waters from 2007 to 2022 using Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) and European Centre of Medium-range Weather Forecasts Reanalysis v.5 (ERA5) data. The results show that in the sea area, the aerosol backscatter coefficient at 532 nm and extinction coefficient at 532 nm increase with increasing RH; the aerosol depolarization ratio decreases with increasing RH. The optical properties of aerosols are generally lower in summer, while they fluctuate with rising RH in other seasons. Notably, the values recorded in 2014–2019 were markedly lower than those in 2007–2013. Nevertheless, from 2020 to 2022, the proportion of aerosol types remained largely stable compared to that of 2014–2019, suggesting a negligible impact of the COVID-19 pandemic on emissions, but the near-shore waters’ aerosol optical properties were more sensitive to minor changes than those of far-off waters. After dividing the China’s offshore waters, the overall optical properties of aerosols decreased in order of the Bohai Sea and Yellow Sea, the East China Sea, and the South China Sea, due to the proportion of marine aerosols increase toward the south. After dividing the altitude layer in the sea area, within the range of 0–7 km, the higher the altitude, the less oceanic aerosols and the more terrestrial aerosols. The aerosol depolarization ratio rises, while the aerosol backscatter coefficient at 532 nm and extinction coefficient at 532 nm alternate downwards. We speculate this is linked to the steep decline in total aerosol content as altitude rises. Our results could provide theoretical references for further deepening the understanding of aerosol generation mechanisms in China’s offshore waters.